Rapid Fabrication of Periodic Patterns on Poly(styrene-co-acrylonitrile) Surfaces Using Direct Laser Interference Patterning. (26th February 2015) - Broglia, Martin F.; Acevedo, Diego F.; Langheinrich, Denise; Perez-Hernandez, Heidi R.; Barbero, Cesar A.; Lasagni, Andrés F.
Abstract : Periodic microstructures in styrene-acrylonitrile (SAN) copolymers are fabricated by two-beam direct laser interference patterning using a nanosecond pulsed laser operating at a wavelength of 266 nm. The SAN copolymers are synthesized using different molar ratios (styrene to acrylonitrile) by a free radical polymerization process. The chemical composition of the copolymers and their properties are determined using Fourier transformed infrared spectroscopy (FTIR) and differential scanning calorimetry (DSC). Depending on the composition of the irradiated copolymer films, with weight ratios ranging from 58 to 96.5% of styrene to acrylonitrile, different ablation behaviors are observed. The laser fluence necessary to locally ablate the copolymer is found to be dependent on the copolymer composition. Unlike other dielectric polymers, the laser irradiation produced both direct ablation of the irradiated material and collapse of the surface. It is shown that, by varying the laser fluence and the copolymer composition, the surface structure can be changed from a periodic pattern with a swelled topography to an ablated-like structure. The number of holes does not depend monotonically on the amount of PS or PAN units but shows a more complex behavior which depends on the copolymer composition and the laser fluence.